High voices - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
With the International Year of the Mountains well on its way, it is essential that mountain people s own stories can be heard loud and clear. At Website: www.mountainvoices.org, operated by Panos, you will find people s testimonies from a dozen...